Cover Image. Issue 12 (29th November 2018) - Eguíluz‐Gracia, Ibon; Malmstrom, Kristiina; Dheyauldeen, Sinan Ahmed; Lohi, Jouko; Sajantila, Antti; Aaløkken, Ragnhild; Sundaram, Arvind Y. M.; Gilfillan, Gregor D.; Makela, Mika; Baekkevold, Espen S.; Jahnsen, Frode L.
Abstract : The cover image is based on the Original Article Monocytes accumulate in the airways of children with fatal asthma by Ibon Eguíluz‐Gracia et al, DOI:https://doi.org/10.1111/cea.13265 .